The transformation of hunger revisited - Ian Gazeley; Andrew Newell; Mintewab Bezabih (Institute for the Study of Labor (IZA), 2013)
We examine Trevon Logan's 2009 claim to have found low levels of nutrition among British worker's households in the late 19th century. Using the same data, we conclude that Logan's estimates are thirty percent too low. Logan buttressed his estimates by claiming that the income elasticity of calories demand was unusually high among these households, relative to other estimates, reflecting great hunger. We find that the elasticity is high, but not outside the range observed in other data sets. We also warn against the simple assertion that a high elasticity implies hunger.
Keywords: I15; I32; N33; 330; nutrition; living standards; worker's households; late 19th century; Britain